Exploring the Condition of Cyberbullying Victimization on Adolescents' Self-Esteem: A Cross-Sectional Study - Dwi Indah Iswanti; Nia Agustiningsih; I Made Moh. Yanuar Saifudin; Ah Yusuf; Ahsan (Universitas STRADA Indonesia, 2025)
Background: Experiencing cyberbullying victimization has psychological repercussions on an individual's self-concept, particularly affecting self-esteem and leading adolescents to withdraw from social interactions. Purpose: This study aim was to explore the conditions of adolescents' experiences as victims of cyberbullying and their self-esteem. Methods: Employing a cross-sectional design, this research encompasses a population of all teenagers from two high schools in East Java, Indonesia, totaling 678 individuals. The sample size of 144 was determined using purposive sampling based on predetermined criteria. The utilized questionnaires include the Demographic Questionnaire, Revised Cyber Bullying Inventory (RCBI), and Coopersmith Self-Esteem Inventory. Descriptive analysis used to provide an overview of the results of the exploration of adolescent victims of cyberbullying and their self-esteem. Results: The most common forms of cyberbullying experienced are harassment, flaming and exclusion. Teenagers who are victims of cyberbullying are mostly in the moderate category, totaling 87 people (60.42%) and most of their self-esteem is in the moderate category, totaling 71 people (49.31%). Conclusion: This underscores the importance of mental health nurses intervening to enhance the self-esteem of adolescents grappling with cyberbullying victimization, ultimately aiming for the attainment of stable self-esteem.